Pengendalian Persediaan Kedelai Sebagai Bahan Baku Tahu (Studi Kasus Industri Tahu Jembar Manah, Kecamatan Sumedang Selatan, Kabupaten Sumedang, Jawa Barat) - Ramadhina, Ratu Rizki; Mukti, Gema Wibawa (Universitas Galuh, 2025)
Soybean is the raw material used in the production of tofu. Jembar Manah Tofu Industry is a producer of sumedang tofu that uses an estimation method in purchasing soybean raw materials. This study aims to analyze the production performance of sumedang tofu and the inventory control of soybeans as raw material, also provide inventory control recommendations to optimize inventory costs in the Jembar Manah Tofu Industry. The research design is qualitative with a case study approach. The data were analyzed using descriptive analysis and the Economic Order Quantity (EOQ) method. The results showed that the materials used in tofu production consist of soybeans, coagulant, coarse salt, and cooking oil. The production process includes washing and soaking, grinding, boiling, filtering, coagulating, molding, cutting, marinating, and frying. The industry currently orders soybeans in quantities of 5,000 kg with a frequency of 12 orders per year and a delivery lead time of 1–2 days. By applying the EOQ method, the optimal purchase quantity is 2,484 kg with a frequency of 18 orders per year, safety stock of 250 kg, and reorder point of 500 kg. EOQ implementation can reduce total inventory costs by 20,31%, demonstrating its potential to address uncertainties in the procurement of soybean raw materials.